Amyloid-like Fibrils from an α-Helical Transmembrane Protein - Stroobants, Karen (Biochemistry, 2017)
[Image: see text] The propensity to misfold and self-assemble into stable aggregates is increasingly being recognized as a common feature of protein molecules. Our understanding of this phenomenon and of its links with human disease has improved substantially over the past two decades. Studies thus far, however, have been almost exclusively focused on cytosolic proteins, resulting in a lack of detailed information about the misfolding and aggregation of membrane proteins. As a consequence, although such proteins make up approximately 30% of the human proteome and have high propensities to aggregate, relatively little is known about the biophysical nature of their assemblies. To shed light on this issue, we have studied as a model system an archetypical representative of the ubiquitous major facilitator superfamily, the Escherichia coli lactose permease (LacY). By using a combination of established indicators of cross-β structure and morphology, including the amyloid diagnostic dye thioflavin-T, circular dichroism spectroscopy, Fourier transform infrared spectroscopy, X-ray fiber diffraction, and transmission electron microscopy, we show that LacY can form amyloid-like fibrils under destabilizing conditions. These results indicate that transmembrane α-helical proteins, similarly to cytosolic proteins, have the ability to adopt this generic state.